2017
DOI: 10.1021/acs.jnatprod.6b00973
|View full text |Cite
|
Sign up to set email alerts
|

Antitubercular Activity of Mycelium-Associated Ganoderma Lanostanoids

Abstract: In a continuation of our research into antitubercular lanostane triterpenoids from submerged cultures of Ganoderma species, three strains, Ganoderma orbiforme BCC 22325, Ganoderma sp. BCC 60695, and Ganoderma australe BCC 22314, have been investigated. Fourteen new lanostane triterpenoids, together with 35 known compounds, were isolated. Antitubercular activities of these mycelium-associated Ganoderma lanostanoids against Mycobacterium tuberculosis H37Ra were evaluated. Taken together with the assay data of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 21 publications
(61 reference statements)
0
25
0
Order By: Relevance
“…We previously reported antimalarial and antitubercular activities of lanostane triterpenoids isolated from cultures of Ganoderma species that are close in macro-and micromorphology to the medicinal mushroom Ganoderma lucidum. 9 Compounds isolated in the present study were primarily more oxygenated and modified than those from the major group of Ganoderma species. Isolated compounds with sufficient sample quantities (37 compounds) were tested for antimalarial activity against Plasmodium falciparum K1 (multidrug-resistant strain), antitubercular activity against Mycobacterium tuberculosis H37Ra, and cytotoxicity to nonmalignant Vero cells (African green monkey kidney fibroblasts) (Table 3).…”
Section: Journal Of Natural Productsmentioning
confidence: 55%
See 1 more Smart Citation
“…We previously reported antimalarial and antitubercular activities of lanostane triterpenoids isolated from cultures of Ganoderma species that are close in macro-and micromorphology to the medicinal mushroom Ganoderma lucidum. 9 Compounds isolated in the present study were primarily more oxygenated and modified than those from the major group of Ganoderma species. Isolated compounds with sufficient sample quantities (37 compounds) were tested for antimalarial activity against Plasmodium falciparum K1 (multidrug-resistant strain), antitubercular activity against Mycobacterium tuberculosis H37Ra, and cytotoxicity to nonmalignant Vero cells (African green monkey kidney fibroblasts) (Table 3).…”
Section: Journal Of Natural Productsmentioning
confidence: 55%
“…These studies have resulted in the isolation of lanostane triterpenoids from mycelial cultures, and many of them exhibited antimalarial and antitubercular activities. 9 In continuation of this research, we have been expanding the targets into other species in the family Ganodermataceae. We report here the isolation of 31 new highly modified lanostane triterpenoids (1−31) together with 19 known compounds (32−50) from natural fruiting bodies of a Tomophagus sp., which were collected from a dead oil palm tree.…”
mentioning
confidence: 99%
“…Furthermore, terpenoids, which were isolated from various natural sources, e.g., medicinal plants, fungi, and marine organisms also displayed a promising and interesting antitubercular activity against different strains of M. tuberculosis [ 43 47 ]. Recently, Isaka and coworkers [ 44 , 45 ] reported a potent antitubercular activity of several lanostane triterpenoids isolated from different cultures of Ganoderma species with MIC values ranging between 0.78 and 12.5 μ g/ml. In addition, a lot of isolated alkaloids belonging to various classes, e.g., indole, pyrrole, indoloquinoline, carbazole, manzamine, quinoline, isoquinoline, and pyrrolidine alkaloids were investigated for their antimycobacterial activities against M. tuberculosis , where many of them exhibited a notable and potent efficacy and may be regarded as lead molecules for the treatment of tuberculosis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mushroom specimen was deposited in the BIOTEC Bangkok Herbarium as BBH 19074, and the living culture was deposited in the BIOTEC Culture Collection as BCC 22314. Identification of this fungus is based on the morphology and ITS rDNA sequence data (GenBank accession number: KX421866) [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…A number of lanostanes and modified lanostanes have been isolated from natural or cultivated fruiting bodies and/or mycelial cultures of this genus [ 3 , 4 ]. We previously reported that several lanostanes from mycelial cultures of Ganoderma species exhibit significant growth inhibitory activities against Mycobacterium tuberculosis H37Ra [ 5 7 ]. In the conclusive full paper [ 5 ], the structure–activity relationships (SARs) of the natural lanostanes were proposed, wherein (24 E )−3β,15α-diacetoxylanosta-7,9(11),24-trien-26-oic acid (ganodermic acid S, 1 ) was the optimal anti-TB Ganoderma lanostanoid (Fig.…”
Section: Introductionmentioning
confidence: 99%